FROM GRID COMPUTING TO CLOUD INFRASTRUCTURES (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
As a consequence of the economic crisis, the funds allocated for the development of the IT&C infrastructure in all domains become scarcer, whilst the need for computing services increases day by day and becomes a key factor in the existence and success of any institution or company.In the later years, new computing technologies have reached the market, technologies that allow transparent sharing of the physical resources and of the services for their users, like Grid computing paradigms, and lately Cloud infrastructures.In this paper we will conduct a comparative analysis of the architectures and services offered by the two kinds of technologies, aiming to determine if they can give a real competitive advantage to the academic environments through their cost/performance benefits.